2011
DOI: 10.1074/jbc.m110.189936
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase PC7 Enhances the Activation of the EGF Receptor Pathway through Processing of the EGF Precursor

Abstract: Although the processing profile of the membrane-bound epidermal growth factor precursor (pro-EGF) is tissue-specific, it has not been investigated at the cellular level nor have the cognate proteinases been defined. Among the proprotein convertases (PCs), only the membrane-bound PC7, the most ancient and conserved basic amino acid-specific PC family member, induces the processing of pro-EGF into an ϳ115-kDa transmembrane form (EGF-115) at an unusual VHPR 290 2A motif. Because sitedirected mutagenesis revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 81 publications
(75 reference statements)
2
19
0
Order By: Relevance
“…10) (44). However, it is equally probable that in vivo PCSK7 promotes the TGF␤1a function in an indirect manner that does not involve direct proteolysis (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) (44). However, it is equally probable that in vivo PCSK7 promotes the TGF␤1a function in an indirect manner that does not involve direct proteolysis (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the activity of PCSK7 can be replaced in the site-specific cleavage of pro-BMP4 (15), pro-PDGF (16), pro-NGF (17,18), and pro-VEGF-C (19). However, PCSK7 seems to be solely responsible for rescuing an unstable MHC I in post-endoplasmic reticulum compartments (20) and for the proteolysis of pro-EGF (21). In addition, a genome-wide association study recently revealed that an SNP (rs236918) in the PCSK7 gene region is associated with an increase in the serum level of soluble transferrin receptor, thus implying that PCSK7 could have a role in iron metabolism in humans (22).…”
mentioning
confidence: 99%
“…Thus, pro-BMP10 processing requires membrane association of furin. The intracellular cleavage of pro-BMP10 by furin was further confirmed by the inability of D6R to inhibit the pro-BMP10 processing in CHO-FD11 overexpressing either furin CT-PC7 or furin TMCT-PC7 (not shown), although the latter chimera is mostly localized at the cell surface (34).…”
Section: Processing Of Human Pro-bmp10 By Furin Pace4 and Pc5/6 Occmentioning
confidence: 98%
“…It has been demonstrated that PC7 reaches the cell surface via the conventional route as well as via a brefeldin A-and coat protein complex II (COPII)-independent unconventional secretory pathway (12). Furthermore, it has been suggested that pro-EGF processing by full-length membrane-bound PC7 does not occur at the cell surface but that it requires endocytosis into clathrin-coated pits (29). In this study, the endocytosis of PC7 from the plasma membrane was investigated by means of cell fractionation, antibody uptake experiments, and cell surface biotinylation.…”
mentioning
confidence: 99%